Growth Response of Robusta Coffee (Coffea canephora) Cuttings to Arbuscular Mycorrhizal Fungi Dosage Application in Ultisol - Husna; Hafiz Luthfi; Sismita Sari; AH. Maftuh Hafidh Zuhdi (Agricultural Science, 2026)
Coffee production in Lampung Province faces significant challenges due to the dominance of Ultisol soils characterized by low fertility, high acidity, and phosphorus fixation. This study aimed to determine the optimal dosage of arbuscular mycorrhizal fungi (AMF) inoculum to enhance the growth of robusta coffee (Coffea canephora) cuttings in Ultisol growing media. The experiment was conducted at the State Polytechnic of Lampung from August to October 2025 using a Randomized Complete Block Design (RCBD) with four treatments: M0 (control without mycorrhizal), M1 (10 g mycorrhizal inoculum per plant), M2 (20 g per plant), and M3 (30 g per plant). Each treatment was replicated four times with three plants per experimental unit. Growth parameters measured included leaf number, plant height, and root volume at 0, 3, 9, and 12 weeks after transplanting. Results showed that the M1 treatment consistently produced superior growth performance across all parameters. At 12 weeks after transplanting, M1 achieved 21.44 leaves (53.1% increase), 38.69 cm plant height (48.7% increase), and 44.67 cm³ root volume (108.3% increase) compared to the control. Higher dosages (M2 and M3) showed diminishing returns, indicating excessive inoculum application may cause unfavorable carbon allocation dynamics. This study concludes that 10 g mycorrhizal inoculum per plant is the optimal dosage for enhancing robusta coffee cutting growth in Ultisol nursery systems.